TRAINING ON CALCULATION COST OF PRODUCTION FOR NUT PEAK MSMES IN LHOKSEUMAWE CITY - Rico Nur Ilham; Irada Sinta; Amru Usman; Em Yusuf Iis; Rusydi Abubakar (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
One of the fundamental problems faced by MSME players is a lack of ability in accounting, including calculating the cost of goods manufactured correctly. This phenomenon shows that there are still many MSME actors who have not been able to obtain optimal profits because of their inability to calculate the cost of production correctly. Calculating the cost of production is very important considering that the benefit of information on the cost of production is to determine the selling price of the product. Errors in calculating the cost of production will cause errors in determining the selling price of the product. Ibu Yati's Peanut Rempeyek MSME is one of the MSMEs engaged in the production and sale of various wet cakes and pastries. The results of the service team's initial communication with Mrs. Yati's Peanut Rempeyek showed that this business had never calculated the cost of production for the products it produced because the owner did not have an understanding of the importance of calculating the cost of production. Under these conditions, it is difficult for MSMEs to develop and set selling prices that compete in the market with other products so that maximum profits can be obtained. Based on the problems faced by Ibu Yati's Rempeyek Nut SMEs, the main solution that can be provided to overcome the problems faced by Ibu Yati's Rempeyek Nut SMEs is the application of the calculation of the cost of production for the products they produce which includes identifying production costs and calculating the cost of production. The output resulting from this solution for Mrs. Yati's peanut brittle UMKM is the availability of basic production cost calculations for each type of product produced by Mrs. Yati's peanut brittle UMKM.